Prevalencia de malnutrición y evaluación de la prescripción dietética en pacientes adultos hospitalizados en una institución pública de alta complejidad (2007)
ABSTRACT: Malnutrition in hospitalized patients is a common problem generally associated with morbidity increasing, mortality, complications and stay days; nevertheless it neither is diagnosed, nor opportunely treated. objective: To determine malnutrition prevalence and evaluate the dietary treatment of energy and proteins for hospitalized adult patients in a public institution of high complexity. Methodology: Descriptive observational cross-sectional study. There was evaluated nutritional status of 138 hospitalized adult patients during the first 48 hours of admission, using the Global Subjective Estimate (GSE). Energy and proteins contribution of the prescribed diet was determined and it was compared with the requirement. Results: risk or malnutrition were presented in 63% of the patients, without difference for age (p=0.12), nor for service (p=0.249). Energy and protein prescription were inadequate in 56% and 70% of the patients respectively, with significant differences according to the professional (p=0.0000). There were no differences between the correct prescription and the nutritional status for energy (p=0.42) not for proteins (p=0.23). Conclusions: Malnutrition prevalence by using GSV parameter in hospitalized adult patients was elevated. The majority of cases the dietary tratment was not adjusted to energy and proteins requirements. Key words: malnutrition, protein-energy malnutrition, diet therapy, energy, protein, nutrition assessment, inpatient, hospitalization, adult.